Perception of Deqi by Chinese and American acupuncturists: a pilot survey - Fang Jiliang; Li Ming; Vangel Mark G; Sporko Tara N; Hui Kathleen KKS; Lao Lixing (Chinese Medicine, 2011)
Abstract Background In acupuncture, deqi is the sensory experience related to clinical efficacy. As the first study taking into account cultural differences on deqi sensation, this pilot survey aims to corroborate the acupuncturists' general experience in clinical practice with functional magnetic resonance imaging (fMRI) findings. Methods Questionnaires were distributed to acupuncturists of TCM (traditional Chinese medicine)hospitals and acupuncturists attending workshops and seminars in the United States and China. Questions covered clinical significance of deqi, patient attitude and the nature of some pain-related sensations elicited by manual needling. Results 47 out of a total of 86 acupuncturists agreed that dull pain was deqi and over half regarded it beneficial, while sharp pain was non-deqi and harmful instead. The patients' attitude toward deqi sensation showed a difference between US and China. There was no other dimension showing a difference. Conclusion Results of this pilot survey indicate that the acupuncturists' perception is consistent with our previous fMRI findings. Results showed almost complete agreement that dull pain is considered deqi and beneficial to treatment, while sharp pain is not deqi and harmful. Particularly, dull pain was deqi and was beneficial to treatment whereas sharp pain was not. Patients in China liked the deqi experience whereas those in the US did not.